Genetic parameter estimates for growth traits and Kleiber ratio in Hairy goat in Türkiye - Güngör, İ and Alkoyak, K and Koncagül, S (Journal of the Hellenic Veterinary Medical Society, 2025)
This research was carried out to evaluate the environmental factors affecting the growth characteristics and Kleiber ratio (KR) before and after weaning in Hair goats and to estimate the related genetic parameters. The data were obtained from the subproject carried out in Kahramanmaraş region on Hairy goat included in “the National Genetic Improvement Project of Sheep and Goat in Farmer Conditions (NGIPSG)” in Türkiye which has been supported by the General Directorate of Agricultural Research and Policies (TAGEM). The fixed effects included in the analysis were flock-year of birth, birth season, age of mother, type of birth and sex of kids. The all fixed factors were significant on live weight of kids and KR before and after weaning (P<0.05). Direct heritabilities were 0.27, 0.23, 0.23, 0.22, 0.21, 0.39, 0.37 and 0.20 for birth weight (W0), weight at 60 days of age (W60), daily weight gain from birth to 60 days of age (DWG60), weight at 120 days of age (W120), daily weight gain from birth to 120 days of age (DWG120), weight at 180 days of age (W180), Kleiber Ratio at 60 days of age (KR60) and Kleiber Ratio at 120 days of age (KR120), respectively. The genetic and the environmental correlations among all traits were positive, except for W0 that environmental correlations between W0 with the all other traits were small and negative. Based on the results in this study, it was concluded that it will be more effective to select kids based on KR60 in order to increase body weight at butchery age.